Optimal test for PAR(1) dependence against PSETAR(2, 1, 1) models with specified threshold. Issue 4 (16th February 2016) - Merzougui, M.
Abstract: This paper is devoted to testing a classical periodic autoregressive against a periodic threshold autoregressive modelwith specified threshold . The local asymptotic normality property is shown via the adapted sufficient conditions due to Swensen (1985 ). Using this result we consider the case where the innovation density is specified, and we obtain a parametric local asymptotic " most stringent " test.